Social capital of an enterprise = Kapitał społeczny przedsiębiorstwa - Wyrwa, Joanna (Zielona Góra: Faculty of Economics and Management Press)
The enterprise is presently perceived as a source of social capital development. The development of social capital within an enterprise is visible through the increase of level of potential of its dimensions, e.g. increase of the level of trust in interpersonal contacts, striking a bigger number of close contacts with coworkers, or developing by the employees' new capabilities and competencies.
Keywords: kapitał społeczny; przedsiębiorstwo; wartości niematerialne; social capital; enterprises; intangible assets